Comparison of Serum Lipid Levels between Ischemic and Haemorrhagic Stroke Patients: An Observational Study - Khan, Asma; Ahammad, Benzir; Pondit, Proshanta Kumar; Islam, M M Shahin Ul; Saha, Radheshyam; Arif, Khan Mohammad; Hossain, Ahmed Manadir; Seyam, Tanzim Ahmad (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Stoke is the leading cause of adult disability and the second leading cause of mortality. The incidence of stroke has decreased in the developed world but increased in developing countries like Bangladesh. Association between serum lipid levels and stroke is controversial and regional data is limited. In this study, we aimed to compare the difference in serum lipid levels among ischemic stroke (IS) and hemorrhagic stroke (HS) patients. This cross-sectional observational study was conducted at Bangabandhu Sheikh Mujib Medical College Hospital, Faridpur, from February to June, 2021. Admitted 50 consecutive IS patients, and 50 HS patients were enrolled. After clinical and radiological confirmation, detailed history was taken and 8 hours of fasting blood sample for serum lipid profiling were collected. Data were analyzed to observe the difference in lipid levels between the two groups. Among the 100 stroke patients mean age of the IS and HS groups was 67.62 ± 8.33 and 65.14 ± 9.43 years, respectively. Males were predominant in both groups, and the majority of them had a history of hypertension. Mean serum total cholesterol (TC) was above the normal range in IS group (5.28 ± 2.18 mmol/L), and serum high density lipoprotein (HDL) was lower in IS group (0.82 ± 0.28 mml/L), and both differences were statistically significant between the IS and HS groups. This study found that patients with IS had a higher incidence of abnormal TC and HDL levels. Preventive measures using lipid-lowering agents can be considered for high-risk patients. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):83-87